The National Institute for Occupational Safety and Health B Reader Certification Program-An Update Report (1987 to 2018) and Future Directions - Halldin, Cara N; Hale, Janet M; Weissman, David N; Attfield, Michael D; Parker, John E; Petsonk, Edward L; Cohen, Robert A; Markle, Travis; Blackley, David J; Wolfe, Anita L; Tallaksen, Robert J; Laney, A Scott (Journal of occupational and environmental medicine, 2019)
The National Institute for Occupational Safety and Health (NIOSH) B Reader Program provides the opportunity for physicians to demonstrate proficiency in the International Labour Office (ILO) system for classifying radiographs of pneumoconioses. We summarize trends in participation and examinee attributes and performance during 1987 to 2018. Since 1987, NIOSH has maintained details of examinees and examinations. Attributes of examinees and their examination performance were summarized. Simple linear regression was used in trend analysis of passing rates over time. The mean passing rate for certification and recertification for the study period was 40.4% and 82.6%, respectively. Since the mid-1990s, the number of B Readers has declined and the mean age and years certified have increased. To address the declining B Reader population, NIOSH is currently taking steps to modernize the program and offer more opportunities for training and testing.